Innovation, research and development in Romanian enterprises - BARNA, Cristina; EPURE, Manuela; BAICU, Claudia (Annals of Spiru Haret University. Economic Series, 2010)
The European Union declared the year 2009 – The Year of Creativity and Innovation. Creativity and innovation can move society forward toward prosperity. In this context, we analyzed in our paper the innovation, research & development potential and performance of the Romanian enterprises. After presenting the conceptual framework and statistical sources in EU for innovation and a general overview of Europe seen as a place for research activities, we examined in details the Romania case: a country still in the group of catching-up countries, but one of the growth leaders among this group. In the last part of the paper we focused on research and development data analysis for the 2003-2008 interval, at enterprise level, also with commentaries about the economic and financial crisis impact.